Dahlica goltella sp. n., a new bagworm species from Slovenia (Lepidoptera: Psychidae) - Rekelj, Jurij (Acta entomologica slovenica (Ljubljana), 2014)
The description and illustrations of a new species Dahlica goltella sp. n. from Slovenia are provided. Morphological differences between related species of Dahlicini are presented and figured. Results of DNA barcoding analysis are shown. Data on the diagnosis, distribution and biology of the new species are given.
Keywords: COI; Dahlica goltella; DNA barcoding; DNA molekularna analiza; Lepidoptera; metulji; new species; nova najdbe; Psychidae; Slovenia; Slovenija